The state of the evidence about the Synergy Model for patient care. (25th September 2020) - Nania, T.; Barello, S.; Caruso, R.; Graffigna, G.; Stievano, A.; Pittella, F.; Dellafiore, F.
Abstract : Aim: To systematically and critically summarize the state of the evidence about the Synergy Model and its utilization in nursing practice. Background: The Synergy Model emphasizes the importance of alignment between patient needs and nurse competencies in achieving adequate patient‐ and nurse‐related outcomes. It is a relatively new patient‐centred care model developed at the end of the 1990s. Introduction: Despite the Synergy Model's potential to support patient‐centred care, its practical application is still mainly limited. Thus far, literature about the Synergy Model has not yet been synthesized, undermining its broader utilization globally. Methods: A systematic search was performed on the following databases: PubMed, CINAHL and Scopus. The authors used the Preferred Reporting Items for Systematic Reviews and Meta‐analyses (PRISMA) statement and checklist to guide the systematic search; 26 papers were included in this study. A critical interpretative synthesis was adopted to summarize the data extracted from the included papers. Results: Five interpretative themes emerged: conceptualization, experiences from the field, nursing education, patient‐related outcomes and system‐related outcomes. Synergy Model shows a precise theoretical definition, and it was implemented in multiple clinical settings, mainly in critical care contexts. It seems to have a positive influence on patient‐related, nurse‐related and system‐related outcomes. Discussion: Synergy Model seems to be positively associated with specific susceptible outcomes, such as patient satisfaction, reduction of patient's complications, staff satisfaction, empowerment, and engagement of patients and healthcare providers. However, the level of evidence is still limited. Conclusion: Future international research should demonstrate the feasibility of implementing the Synergy Model at an international level. More empirical research is needed to demonstrate the effectiveness of the model on susceptible outcomes. Implications for nursing and health policy: This systematic review could support further development of international programmes based on the Synergy Model. The Synergy Model's implementation has the potential to optimize nursing competencies, patient‐ and nurse‐related outcomes.